Critical Criticism of the Interpretation of Usury by Al-Jashshash in Tafsir Ahkam al-Qur'an - Mauluddin, Moh (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
AbstractTafsir Ahkam Al-Qur'an by Al-Jashshash is an important reference in understanding the laws related to usury in the Qur'an. Al-Jashshash, a 4th century Hanafi scholar, focuses on the interpretation of Qur'anic verses related to law, especially usury. This research aims to critically analyze Al-Jashshash' interpretation, including the arguments and proofs he used, and evaluate the criticisms by using a qualitative method with a literature study. In addition, this study also examines the relevance of Al-Jashshash' interpretation in the context of modern economics, especially regarding the concept of 'required addition' in the definition of usury, which emphasizes exploitation and injustice in financial transactions, and its implications for current Islamic financial practices. The results of this study show that his interpretation has been criticized, especially regarding methodological inconsistencies, fanaticism towards the Hanafi school, and inaccuracy of interpretation in several cases, especially the concept of 'required addition' in defining usury which has been debated, especially in the context of modern economics.Keywords: Al-Jashshash; Critique of Interpretation; Islamic Economics; Tafsir of the Rules of the Qur'an; Usury. AbstrakTafsir Ahkam Al-Qur'an karya Al-Jashshash merupakan rujukan penting dalam memahami hukum-hukum terkait riba dalam Al-Qur'an. Al-Jashshash, ulama mazhab Hanafi abad ke-4 Hijriah, fokus pada penafsiran ayat-ayat Al-Qur'an yang berkaitan dengan hukum, terutama riba. Penelitian ini bertujuan untuk menganalisis secara kritis penafsiran Al-Jashshash, termasuk argumen dan dalil yang digunakannya, serta mengevaluasi kritik-kritik tersebut dengan menggunakan metode kualitatif dengan studi kepustakaan. Selain itu, penelitian ini juga mengkaji relevansi penafsiran Al-Jashshash dalam konteks ekonomi modern, terutama terkait konsep 'tambahan yang disyaratkan' dalam definisi riba, yang menekankan pada eksploitasi dan ketidakadilan dalam transaksi keuangan, serta implikasinya terhadap praktik keuangan Islam saat ini. Hasil penelitian ini menunjukkan bahwa penafsirannya menuai kritik, terutama terkait inkonsistensi metodologis, fanatisme terhadap mazhab Hanafi, serta ketidaktepatan penafsiran dalam beberapa kasus, terutama konsep 'tambahan yang disyaratkan' dalam mendefinisikan riba yang menuai perdebatan, terlebih dalam konteks ekonomi modern. Kata Kunci: Al-Jashshash; Ekonomi Islam; Kritik terhadap Tafsir; Riba; Tafsir atas Aturan-aturan Al-Qur'an.